2022
DOI: 10.1093/cvr/cvac093
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity-associated atrial fibrillation: molecular determinants, mechanisms, and clinical significance

Abstract: Obesity is an important contributing factor to the pathophysiology of atrial fibrillation (AF) and its complications by causing systemic changes, such as altered haemodynamic, increased sympathetic tone, and low-grade chronic inflammatory state. In addition, adipose tissue is a metabolically active organ that comprises various types of fat deposits with discrete composition and localization that show distinct functions. Fatty tissue differentially affects the evolution of AF, with highly secretory active visce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 164 publications
0
19
0
Order By: Relevance
“…The cellular mechanisms by which EAT modulates cardiomyocyte calcium handling, indirectly by adipokines or directly by structural changes, are not as well studied. The reader is referred to Antonopoulos and Antoniades [ 11 ] for a detailed review of the current understanding of cellular mechanisms within EAT, cardiomyocytes, and fibroblasts within the myocardium and Gawałko et al [ 77 ] for a detailed review of the mechanistic changes underlying AF in obese patients.…”
Section: Pathophysiologic States Of Epicardial Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…The cellular mechanisms by which EAT modulates cardiomyocyte calcium handling, indirectly by adipokines or directly by structural changes, are not as well studied. The reader is referred to Antonopoulos and Antoniades [ 11 ] for a detailed review of the current understanding of cellular mechanisms within EAT, cardiomyocytes, and fibroblasts within the myocardium and Gawałko et al [ 77 ] for a detailed review of the mechanistic changes underlying AF in obese patients.…”
Section: Pathophysiologic States Of Epicardial Adipose Tissuementioning
confidence: 99%
“…Other studies have also reported the paracrine mediators secreted from EAT had similar effects of conduction slowing and AP prolongation [76], suggesting more pathogenic mechanisms than purely mechanical. However, other reports suggest that AP duration is reduced, which is considered a more common pathological change in the development of AF [58,59,77]. For example, Martinez-Mateu et al reported that in the atria of obese guinea pigs fed a high-fat diet, rapid pacing was associated with reduced voltage-gated potassium and L-type calcium current, with shortened AP duration and increased incident of afterdepolarizations [78].…”
Section: Epicardial Adipose Tissue and Atrial Fibrillationmentioning
confidence: 99%
“…AF is a common cardiac arrhythmia, and inflammatory mechanisms play an important role in its pathogenesis. [1][2][3][4][5][6][7] AF is commonly found in older individuals, and type 2 diabetes, high blood pressure, obesity and genetics are important predisposing factors (Figure 1). [2][3][4] AF increases the risk of heart failure, stroke and thromboembolism, and increases morbidity and mortality in patients with cardiovascular diseases (CVDs).…”
Section: Inflammation In Afmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] AF is commonly found in older individuals, and type 2 diabetes, high blood pressure, obesity and genetics are important predisposing factors (Figure 1). [2][3][4] AF increases the risk of heart failure, stroke and thromboembolism, and increases morbidity and mortality in patients with cardiovascular diseases (CVDs). 5 Inflammation is perhaps the most important determinant of AF and subsequent fibrosis in MI.…”
Section: Inflammation In Afmentioning
confidence: 99%
“…As the body’s largest endocrine organ, adipose tissue is considered as a crucial regulator of AF, which may affect the occurrence, progression, and prognosis of AF ( 4 ). However, due to the broad dispersion of adipose tissue throughout the body and intra-organ location, the visceral fat with high secretory activity around the heart usually has a more practical effect than fat in other parts, promoting atrial remodeling and increasing the susceptibility to AF ( 5 ). As a kind of organ-specific adipose tissue in direct contact with the surface of the heart, epicardial adipose tissue (EAT) can secrete paracrine or endocrine inflammatory cytokines, adipokines, or other factors that influence the health or diseases of the heart ( 6 ).…”
Section: Introductionmentioning
confidence: 99%